Public and Private Activity in Commercial TV Broadcasting - Bodil O. Hansen; Hans Keiding (Copenhagen Business School (CBS), Department of Economics, 2006)
We consider a model of commercial television market, where private broadcasters coexist with a public television broadcaster. Assuming that the public TV station follows a policy of Ramsey pricing whereas the private stations are profit maximizers, we consider the equilibria in this market and compare with a situation where the public station is privatized and acts as another private TV broadcaster. A closer scrutiny of the market for commercial television leads to a distinction between target rating points, which are the prime unit of account in TV advertising, and net coverage, which is the final goal of advertisers. Working with net coverage as the fundamental concept, we exploit the models of competition between public and private price and quantity in order to show that privatization of the public TV station entails a welfare loss and results in TV advertising becoming more expensive.
hdl:10398/7501
Keywords: L11; L33; L82; 330; TV broadcasting; imperfect competition; Ramsey pricing; welfare comparison